Coconut shell derived bioactive compound Oxyresveratrol mediates regulation of Matrix metalloproteinase 9 - DAMU SUNIL KUMAR,; CHINCHU BOSE,; SANU K SHAJI,; NANJAN PANDURANGAN,; GEETHA B. KUMAR,; ASOKE BANERJI,; BIPIN G. NAIR, (International Journal of Pharma and Bio Sciences, 2017)
Cocos nucifera L., a member of the family Arecaceae is an important fruit crop in tropical countries and is known to possess several pharmacological properties. The oil extracted from the coconut shell is used in Unani medicine to treat severe skin diseases. The present study involves bioactivity guided fractionation and characterization of a potent Matrix Metalloprotease 9(MMP-9) inhibitor from coconut shell extract (CSE) .Coconut shell was extracted using soxhlet extractor and was subsequently purified using Sephadex LH 20 column. The effect of the bioactive fraction, F1 was studied on human melanoma cell line, A375. F1 significantly down regulated the activity of MMP-9 which was further corroborated by qRT-PCR studies. A corresponding decrease in the expression of MMP-2, MMP-9 as well as other biomarkers of cancer progression like COX-2, VEGF and EGFR was also seen. Further studies confirmed that F1 inhibited migration of A375 cells and caused cell cycle arrest at G2/M phase. Based on the results obtained, structural characterization of F1was carried out by NMR and LC/MS which resulted in the identification of F1 as oxyresveratrol, a stilbenoid. Further, molecular docking studies demonstrated that oxyresveratrol forms hydrogen bonds with critical amino acid residues present in the catalytic site of both MMP-9 and MMP-2.